DOMINANT FOLLICLE DIAMETER AT INSEMINATION IS RELATED TO POSITIVE PREGNANCY OUTCOME IN DAIRY CATTLE - KAPSE, S; SINGH, M; SHARMA, A; KUMAR, P (The Indian Journal of Animal Reproduction, 2016)
Transrectal ultrasonographic examination of ovaries of thirty dairy cattle, showing clear cervico-vaginal discharge at estrus, was carried out on the day of 1st artificial insemination (AI) to establish a relation between the dominant follicle diameter and subsequent pregnancy. Pregnancy diagnosis was undertaken on day 60 post-AI. The difference (P<0.05) between mean follicular diameter in pregnant (11.53±0.32 mm, n=10) and nonpregnant (10.16±0.35 mm, n=20) cattle suggested a relation between dominant follicle diameter at AI and subsequent pregnancy outcome in dairy cattle.